THU0055 Interstitial pneumonitis associated with rheumatoid arthritis is more prevalent in aged male with a higher RF level, and frequently combined with emphysema. (23rd January 2014) - Matsubara, E.; Okiyama, S.; Inokuma, S.; Onishi, K.; Nakachi, S.; Asashima, H.; Wakabayashi, K.; Hagiwara, K.; Kobayashi, S.
Abstract : Background: Previously well-known "rheumatoid-lung" has been assumed as interstitial pneumonitis (IP). It is not so prevalent in female-majority of rheumatoid arthritis (RA) patients, but rather observed much more in male patients. We have had an impression that IP in male RA patients has a unique feature of concurrent emphysema development. Objectives: To study how frequently, and which pulmonary diseases develop in male RA patients. The background and associated laboratory features were also focused on. Methods: Male RA patients who visited our hospital from Jan., 2006 to Apr., 2011 are included. The similar number of female patients visited us in the same duration was included as the controls. Lung diseases were diagnosed mainly based on the medical records, XP/HRCT findings, and pulmonary function tests results. As the major disease entities, usual interstitial pneumonia (UIP), nonspecific interstitial pneumonia (NSIP), organizing pneumonia (OP), emphysema and pleuritis were intended. Brinkman Index (BI, smoking index), and serum levels of RF, KL-6 and CRP were evaluated. Results: Lung diseases were observed in 27/72 (37.5%) in male and 5/70 (7.1%) in female patients. In male patients, UIP/NSIP was in 20, OP in 3, emphysema in 18, and pleuritis in 1; 12 had both IP and emphysema. In female, UIP was in 2, OP in 2, emphysema in 1, and pleuritis in 1; 1 had both IP and emphysema. The male patients with lung diseases were older than those without them (72.2±10.3 vs. 63.7±12.9 yr.), had a higher serum RF level (511±390 vs.140±141 U/mL), a higher KL-6 level (801±735 vs. 277±179 U/mL), and a higher Brinkman index. Among the cases with stable arthritis, patients with UIP/NSIP/emphysema showed a low CRP level, while those with OP/pleuritis did a high level. Conclusions: Male RA patients had lung diseases at a high rate of over 30%. UIP/NSIP was observed the most, which was frequently combined with emphysema. The male RA patients having a high RF level and a high smoking index might develop UIP/NSIP and the combined emphysema with a high prevalence rate. Such patients showed a high KL-6 level but a low CRP level. Disclosure of Interest: None Declared